Sasanian Persia - Daryaee, Touraj.
1 online resource (248 pages)
Keywords: Of profound importance in late antiquity, the Sasanian Empire is almost completely unknown today, except as a counterpoint to the Roman Empire. What are the reasons for this ignorance and why does the Sasanian Empire matter? In this brilliant and highly readable new history Touraj Daryaee fills a huge gap in our knowledge of world history. He examines the Sasanians' complex and colourful narrative and demonstrates their unique significance, not only for the development of Iranian civilisation but also for Roman and Islamic history. _x000D__x000D_The Sasanians were the last of the ancient Persian dynasties and are best known as the preeminent practitioners of the Zoroastrian religion. In this concise yet comprehensive new book, Touraj Daryaee provides an unrivalled account of Sasanian Persia. Drawing on extensive new sources he paints a vivid portrait of Sasanian life and unravels the divergent strands that contributed to the making of this great Empire. Sasanian Persia is a unique examination of a period of history that still has great significance for a full understanding of modern Iran._x000D__x000D_'Touraj Daryaee synthesizes a new generation of Sasanian scholarship to present the first single volume study of such important history. The author's erudition is very impressive and he masters complex sources with exemplary clarity.' Gene Garthwaite, Professor of History, Dartmouth College_x000D_.